2010
DOI: 10.1111/j.1551-6709.2010.01107.x
|View full text |Cite
|
Sign up to set email alerts
|

Source‐Goal Asymmetries in Motion Representation: Implications for Language Production and Comprehension

Abstract: Recent research has demonstrated an asymmetry between the origins and endpoints of motion events, with preferential attention given to endpoints rather than beginnings of motion in both language and memory. Two experiments explore this asymmetry further and test its implications for language production and comprehension. Experiment 1 shows that both adults and 4-year-old children detect fewer within-category changes in source than goal objects when tested for memory of motion events; furthermore, these groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
80
0
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 94 publications
(95 citation statements)
references
References 48 publications
14
80
0
1
Order By: Relevance
“…There is indeed such evidence: English-speaking children were not consistent in using (from) behind/back in the It is possible to be even more specific about the locus of difficulty children (and, to some degree, adults) face in encoding Occlusion and Cover. Recall that goal scenes have been found to be encoded more precisely in language compared to source scenes: Goal expressions are often shorter and semantically more specific/dedicated compared to source expressions cross-linguistically (Lakusta & Landau, 2005;Papafragou, 2010;Regier & Zheng, 2007). When children have limited access to the most appropriate (in this case, source) expressions, they will co-opt a related term.…”
Section: Containment Expressions: Testing the Motivation Predictionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is indeed such evidence: English-speaking children were not consistent in using (from) behind/back in the It is possible to be even more specific about the locus of difficulty children (and, to some degree, adults) face in encoding Occlusion and Cover. Recall that goal scenes have been found to be encoded more precisely in language compared to source scenes: Goal expressions are often shorter and semantically more specific/dedicated compared to source expressions cross-linguistically (Lakusta & Landau, 2005;Papafragou, 2010;Regier & Zheng, 2007). When children have limited access to the most appropriate (in this case, source) expressions, they will co-opt a related term.…”
Section: Containment Expressions: Testing the Motivation Predictionmentioning
confidence: 99%
“…Both projects study a variety of motion paths such as Containment (e.g., an object moving into another object), Cover (e.g., an object moving under another object), Support (an object moving onto another object), etc. For each path, both goal (e.g., X goes into/onto Y) and source versions (e.g., X comes out of/off of Y) are examined because prior work has indicated that goal information is encoded more precisely in language than source information (Lakusta & Landau, 2005;Papafragou, 2010;Regier & Zheng, 2007).…”
Section: Empirical Focus and Prospectusmentioning
confidence: 99%
See 1 more Smart Citation
“…Ikegami 1987;Ihara and Fuijita 2000;Stefanowitsch and Rohde 2004;Lakusta and Landau 2005;Papafragou 2010; Lakusta and Landau 2012;Lakusta and Carey 2014). In most studies, the wheel shows a clear preference and spins towards the Goal.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, in Greek Path is encoded within the verb whereas Manner appears elsewhere (see Figure 2; see Antonopoulou 1987;Βassea-Bezentakou 1992;Talmy 2000b: 66-67;Papafragou et al 2002;Selimis 2007;Johanson and Papafragou 2010;Papafragou andKatis 2010, among others). This is exemplified in (2): A recent study by Johanson and Papafragou (2010) has shown that the tendency seemingly characterising most languages in making Goal information more prominent may be more or less strong depending upon the Talmian typology of motion: the speakers of a Satellite-framed language (English) employ a larger number of adposition types than the speakers of a Verb-framed language (Greek).…”
Section: Introductionmentioning
confidence: 99%